An Optimized Core Distribution Adaptive Topology Reconfiguration Algorithm for NoC-Based Embedded Systems - Hou, Bowen; Xu, Dali; Fu, Fangfa; Yang, Bing; Niu, Na (Micromachines (Basel), 2025)
In advanced multicore embedded systems, network-on-chip (NoC) is vital for core communication. With a rise in the number of cores, the incidence of core failures rises, potentially affecting system performance and stability. To address the challenges associated with core failures in network-on-chip (NoC) systems, researchers have proposed numerous topology reconfiguration algorithms. However, these algorithms fail to achieve an optimal balance between topology reconfiguration rate and recovery time. Addressing these issues, we propose an adaptive core distribution optimization topology reconfiguration algorithm, which involves the distribution of faulty cores as the main factor for the reconfiguration procedure. This algorithm is based on a 2D REmesh structure to achieve physical topology reconfiguration, optimized through a bidirectional search algorithm, and features an adaptive algorithm for optimizing core distribution. Experimental results show that a 96.70% successful reconfiguration rate with the proposed algorithm can be guaranteed when faulty cores are less than 68.75% of the max faulty cores. In particular, when the faulty cores reach 8 in the 8 × 9 REmesh, the successful reconfiguration rate is 63.60% with the proposed algorithm, which is 14.80% higher than BTTR and 9.30% higher than BSTR. Additionally, the average recovery time of our algorithm is reduced by 98.60% compared with BTTR and by 15.87% compared with BSTR, significantly improving both the performance and reliability in embedded systems.